Implementation Of The Case Based Reasoning (CBR) Expert System Method For Heart Disease Diagnosis Based On Patient Symptom History: Case Study Of Mitra Lewo Clinic - Ikbal Jamaludin; Ahmad Baehaqi; Egi Badar Sambani (LPPM STMIK Mardira Indonesia, 2025)
Cardiovascular disease ranks among the primary causes of mortality in Indonesia. An expedient and precise diagnostic method is crucial, particularly in primary healthcare settings such as Klinik Mitra Lewo, which face constraints on medical personnel. This research aims to develop a web-based expert system using the Case-Based Reasoning (CBR) methodology to support preliminary diagnosis of heart disease based on a patient's symptom history. The CBR approach functions by juxtaposing new patient symptoms with historical cases via the stages of Retrieve, Reuse, Revise, and Retain. This system is developed using an Object-Oriented Software Engineering (OOSE) methodology and implemented in PHP using the CodeIgniter framework. System testing employs black-box testing techniques to verify that each functionality satisfies user requirements. The research findings demonstrate that the system can offer pertinent initial diagnostic recommendations and assist medical professionals in decision-making. Consequently, an expert system can be a valuable asset in healthcare, especially when medical resources are constrained.